Sebaran Limbah Residu CPO (Crude Palm Oil) Bawah Permukaan Tanah Pada PT. SSDP Dengan Aplikasi Geolistrik - Dodi Irwan Siregar; Thamrin Thamrin; Muhammad Edisar (Universitas Riau, 2014)
One of the environmental problems caused by the increasing growth of the industry.Industrial waste generated that goes into the soil can alter soil properties. This studyreviewing the nature of the soil as a result of the distribution of residual waste CPO (CrudePalm Oil) industry mills. This study uses the characteristics of resistivity and soil nutrientproperties. Soil resistivity properties were tested by making a model before and after thedistribution of waste residue does CPO. Then validated against field measurements, fieldmeasurements comparing the data with the model. To see the changes in nutrient content ofsoil Laboratory Testing properties of soil nutrient changes. The results showed that theresistivity properties change and nutrient content of the soil before and after the distributionof waste residue subjected CPO. Soil resistivity values that have mixed by CPO residualwaste is higher than the value of soil resistivity is not mixed waste palm oil residues, while thecontent of soil nutrients among other properties, increasing soil pH, Include content C-Organic (%) / Inceneration, P-Available (ppm) / Bray-1, N-Total (%) / Kjedahl decreaseddramatically.